Analysis of Added Value of Horticultural Lettuce Products (Lactuca sativa L) in Modern Market with Postharvest Handling Process - Sihite, Enike Windari; Aviantara, I G.N.Apriadi; Yulianti, Ni Luh (Jurnal BETA (Biosistem dan Teknik Pertanian), 2018)
<article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:fae0572e-2e95-430f-987d-0f9e7639e3e5-32" data-testid="conversation-turn-66" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:--spacing(4)] @w-sm/main:[--thread-content-margin:--spacing(6)] @w-lg/main:[--thread-content-margin:--spacing(16)] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="95e7ac2e-7cd2-4d75-817d-63603c551b43" data-message-model-slug="gpt-5-mini"> This study aims to examine postharvest handling of lettuce in modern markets until the product is marketed and to determine the added value of postharvest handling calculated through profit margin. The research was conducted from early September to the end of October 2016 using a descriptive method with direct observation and questionnaires for data collection. The study compared postharvest handling in one modern market and traditional markets. Postharvest handling is an effort to provide added value to lettuce. In the modern market, selling 88.99 kg of all types of lettuce is sufficient to recover the cost of postharvest handling, whereas in the traditional market, 121.55 kg must be sold to restore the initial capital. Effective postharvest handling maintains lettuce shelf life and increases consumer attention and profitability in modern markets. The study found differing profit margins, with the modern market achieving 129.87% and the traditional market 25.3%. The high profit margin in the modern market indicates strong sales and the company’s ability to generate high profits at a certain sales level, while the lower margin in traditional markets reflects lower sales or higher costs relative to sales.